Development and trend prospect of “tri-ultra” optical fiber communication system technology - Yonghua FENG; Xiang LI; Quan CAO; Zhixia GUO (Dianxin kexue)
The development of optical fiber communication system was reviewed and the demand and possible solutions of optical fiber communication technology in the next 20 years were introduced by reviewing the development of optical fiber communication system in the past 20 years and the current research status of “ultra-high speed,ultra-large capacity and ultra-long distance” optical fiber communication system.